Combining a Sinus Augmentation With Tooth Transplantation When Replacing a Missing Premolar in a Young Patient - Juslin, Jessica; Teerijoki-Oksa, Tuija; Jääsaari, Päivi; Kurki, Tia; Thorén, Hanna (Wiley, 2026)
This case report reports how tooth transplantation and a graft-free sinus lift were combined due to insufficient bone volume at the recipient site. An unerupted wisdom tooth was autotransplanted to replace a missing upper premolar. First, the donor tooth was exposed and gently mobilized. At the recipient site, there was a thin layer of bone under the maxillary sinus. The lateral window technique was used in the sinus lift. After elevating the mucous membrane of the sinus floor, the bone was prepared to match the measures of the donor tooth. The mucous membrane was slightly perforated. The donor tooth was moved to the recipient site, and the buccal root partially lacked bony coverage. The transplanted tooth was fixated with sutures. At the 4-year follow-up control, the transplanted tooth was fully erupted without any clinical or radiographical signs of pathology. If the periodontal ligament of the transplanted donor tooth is delicately handled, it can preserve and facilitate the growth of the alveolar bone. During follow-up, it was obvious that new bone had formed around the roots of the donor tooth. It is possible to successfully transplant a developing tooth in the maxillary premolar region, although the initial bone volume is insufficient.